Rapamycin: Drug Repurposing in SARS-CoV-2 Infection - Patocka, Jiri; Kuca, Kamil; Oleksak, Patrik; Nepovimova, Eugenie; Valis, Martin; Novotny, Michal; Klimova, Blanka (Pharmaceuticals, 2021)
Since December 2019, SARS-CoV-2 (COVID-19) has been a worldwide pandemic with enormous consequences for human health and the world economy. Remdesivir is the only drug in the world that has been approved for the treating of COVID-19. This drug, as well as vaccination, still has uncertain effectiveness. Drug repurposing could be a promising strategy how to find an appropriate molecule: rapamycin could be one of them. The authors performed a systematic literature review of available studies on the research describing rapamycin in association with COVID-19 infection. Only peer-reviewed English-written articles from the world's acknowledged databases Web of Science, PubMed, Springer and Scopus were involved. Five articles were eventually included in the final analysis. The findings indicate that rapamycin seems to be a suitable candidate for drug repurposing. In addition, it may represent a better candidate for COVID-19 therapy than commonly tested antivirals. It is also likely that its efficiency will not be reduced by the high rate of viral RNA mutation.